2010
DOI: 10.1063/1.3380847
|View full text |Cite
|
Sign up to set email alerts
|

High temperature lead-free relaxor ferroelectric: Intergrowth Aurivillius phase BaBi2Nb2O9–Bi4Ti3O12 ceramics

Abstract: Articles you may be interested inElectric-field-temperature phase diagram of the ferroelectric relaxor system (1 − x)Bi1/2Na1/2TiO3 − xBaTiO3 doped with manganese J. Appl. Phys. 115, 194104 (2014) ͒ Aurivillius phase ceramic has been found to be a relaxor ferroelectric ͑RFE͒ with the highest reported temperature of the maximum of the dielectric permittivity ͑T m ͒ of all of the known RFE systems. Dielectric characterization revealed that it has two dielectric anomalies. The first one is a frequency independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, due to the complexity of the structure, an interesting phenomenon called intergrowth has been reported in Aurivillius compounds181920. It has been demonstrated that the ferroelectricity of 4- and 3-layered intergrowth compounds is larger than that of individual 4- or 3-layered compound2122.…”
mentioning
confidence: 99%
“…Furthermore, due to the complexity of the structure, an interesting phenomenon called intergrowth has been reported in Aurivillius compounds181920. It has been demonstrated that the ferroelectricity of 4- and 3-layered intergrowth compounds is larger than that of individual 4- or 3-layered compound2122.…”
mentioning
confidence: 99%
“…Figure illustrates P ‐ E and I ‐ E loops for BBNO ceramics measured at 10 Hz at two different temperatures (200 and 25°C). The hysteresis loops obtained at 200°C close to T m (241°C at 1 MHz) indicate the lossy dielectric behavior (Figure A). No current peaks associated with ferroelectric domain switching or field‐induced rotation and/or growth for PNRs were detected, even though E max was as high as 89 kV/cm.…”
Section: Resultsmentioning
confidence: 83%
“…It is important in this application that the films have low coercive fields, high remanent polarizations, and are fatigue-free. It has been recently reported that some A-site or B-site substitution in Bi 4 Ti 3 O 12 thin films could improve their ferroelectric and fatigue resistance properties [1][2][3][4][5]. The improvement in these films can be attributed to the enhanced stability of the oxygen in the Ti-O octahedron layer, which is caused by the substitution of stable rare-earth ions for the volatile Bi ions located near the Ti-O octahedron layer.…”
Section: Introductionmentioning
confidence: 96%